Korean Drama Influence on Communication Styles of Female Students at Nawwir Qulubana Islamic Boarding School - Sam'ani, yatimah, Melinda nur khasanah; Muhammad Yusuf (Program Studi Komunikasi dan Penyiaran Islam, Fakultas Dakwah, Institut Agama Islam Sunan Giri Ponorogo, 2025)
This research investigates shifts in communication styles among female students at Pondok Pesantren Nawwir Qulubana Wonosobo, driven by Korean dramas. The rising appeal of K-Dramas in Indonesia highlights a clash between pesantren principles of modesty and politeness and the emotive Korean ways of speaking. Employing a qualitative phenomenological method, the study delves into how these students balance Korean pop culture with pesantren traditions. Findings reveal that female students incorporate Korean terms like